Activation of PPARδ attenuates neurotoxicity by inhibiting lipopolysaccharide‐triggered glutamate release in BV‐2 microglial cells. Issue 7 (12th March 2018) - Lee, Won Jin; Ham, Sun Ah; Yoo, Hyunjin; Hwang, Jung Seok; Yoo, Taesik; Paek, Kyung Shin; Lim, Dae‐Seog; Han, Sung Gu; Lee, Chi‐Ho; Hong, Kwonho; Seo, Han Geuk
Abstract: Neuroinflammation‐associated release of glutamate from activated microglia has been implicated in the progression of neurodegenerative diseases. However, the regulatory mechanisms underlying this glutamate release are poorly understood. Here, we show that peroxisome proliferator‐activated receptor delta (PPARδ) modulates neurotoxicity by inhibiting glutamate release in lipopolysaccharide (LPS)‐activated BV‐2 microglial cells. Activation of PPARδ by GW501516, a specific PPARδ agonist, inhibited glutamate release in BV‐2 cells. This effect of GW501516 was significantly blocked by shRNA‐mediated knockdown of PPARδ and by treatment with GSK0660, a specific PPARδ antagonist, indicating that PPARδ is associated with blockade of glutamate release. Additionally, GW501516‐activated PPARδ suppressed generation of reactive oxygen species and expression of gp91phox, a functional subunit of NADPH oxidase 2, in BV‐2 cells stimulated with LPS. The inhibitory effect of GW501516 on gp91phox expression and glutamate release was further potentiated in the presence of AG490, a specific inhibitor of janus kinase 2 (JAK2), leading to the inhibition of signal transducer and activator of transcription 1 (STAT1). By contrast, GW501516 upregulated the expression of suppressor of cytokine signaling 1 (SOCS1), an endogenous inhibitor of JAK2. Furthermore, neurotoxicity induced by conditioned media from LPS‐stimulated BV‐2 cells was significantly reduced when conditioned media from BV‐2 cells treated with both LPS and GW501516 were used. These results indicate that PPARδ attenuates LPS‐triggered neuroinflammation by enhancing SOCS1‐mediated inhibition of JAK2/STAT1 signaling, thereby inhibiting neurotoxicity associated with glutamate release. Abstract : The present study showed that PPARδ attenuates LPS‐triggered neuroinflammation by enhancing SOCS1‐mediated inhibition of JAK2/STAT1 signaling, thereby inhibiting neurotoxicity associated with glutamate release.